Older consumers' customer service preferences - Pettigrew, Simone (Springer, 2008)
Older consumers have distinct customer service preferences that can constitute a source of competitive advantage for forward-thinking marketers who seek to attract this large and relatively affluent segment. This chapter focuses on the supermarket, financial planning, and healthcare industries to demonstrate the importance of providing personalized attention to allow for the older person’s deteriorating physical and cognitive abilities and shrinking social networks. In particular, emphasis is placed on the need to allow older customers to form meaningful relationships with service staff. This strategy has implications for the recruitment, training, and retention of staff members who are able to demonstrate genuine concern for the welfare of the older consumer.